Assessment of groundwater potentials of Abuja environs - Martin O. Eduvie; T. Olabode; O.O. Yaya (2003)
This paper assesses the groundwater potentials of Abuja and it’s Environs. The study area is located in the centre of the country. It covers an approximate area of about 7400sqm. It is bounded in the North by Kaduna, in the East by Nassarawa, in the southwest by Kogi and in the west by Niger State respectively. The general elevation of the study area varies considerably. Several rivers and their tributaries drain the area, the major rivers include River Usman, Jabi and Dwako.